(untitled) (Journal of Pharmaceutical Negative Results, 2021)
Background: PMDD is a more severe condition than PMS, and it involves mood swings and a person's ability to function normally. Although medications are usually administered, there has been growing concern for the use of CBT, which is a non-medication-based treatment. Objective: This study objective is to assess the applicability of CBT on PMDD patients with 105 participants registered in the study. Study Design: A Randomized Controlled Trial. Duration and Place of the Study: Department of Psychiatry & GYNAE & OBS Mardan Medical Complex (MMC) Mardan, Pakistan, duration of study from 8th Jan 2020 to 7th Jan 2021. Material and Methods: A total of 105 patients aged 18–45 years with a confirmed diagnosis of PMDD based on DSM-5 criteria were included in this study. This study recruited 105 participants of which 52 participants were randomly assigned to the CBT group while 53 participants were randomly assigned to the control group which was given standard care. Specifically, the CBT intervention involved twelve sessions; each session was conducted in a week spanning three months, and it included elements of cognitive restructuring, stress management, and behavioral activation. The efficacy outcomes were based on the DRSP scale, which measures the severity of PMDD symptoms, and the Q-LES-Q, which measures overall quality of life. Results: Among 130 candidates identified during the preliminary screening, 105 were recruited to the study and were randomly allocated to the CBT group (n=52) and the standard care group (n=53). The mean baseline DRSP was 68.3 ± 12.5 for the CBT group and 69.1 ± 13.0 for the control group, with no significant difference between the groups (p=0.72). Conclusion: It is evident according to the study that CBT is a useful treatment model toward the lessening of severity of PMDD symptoms and the improvement of the quality of life of the patients.